Rapid quantitation of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and its metabolite 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) in rat urine using ultra-fast liquid chromatography mass spectrometry (UFLC/MS/MS). Issue 8 (9th May 2018) - Sepehr, Estatira; Woodling, Kellie A.; Bryant, Matthew S.
ABSTRACT: The tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is a component of tobacco smoke and is rapidly metabolized to 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL). Limited information is available on the relative systemic exposures resulting from NNK administration via the oral, intraperitoneal injection, and inhalation routes. Moreover, there is a need for a rapid method for simultaneous quantitative analyses of NNK and NNAL in rat urine. We developed a method based on Ultra Fast Liquid Chromatography Mass Spectrometry (UFLC/MS/MS) for the extraction and analysis of the potent lung carcinogens NNK and NNAL. Following addition of synthetic labeled internal standards, urine was introduced to 96 well plate Evolute ® Express CX 30 mg solid phase extraction system. The eluates were dried under vacuum and reconstituted in mobile phase before injecting to the LC system. The use of UFLC allowed for a 7.1 min run time. The precision and accuracy of the samples was 1.2-6.6% relative standard deviation (%RSD) and 91-113% of the concentration added, respectively. The limits of detection for NNK and NNAL were 70 and 3.0 pg/mL, respectively. The selectivity and sensitivity of this method improves the ability to measure these compounds at low concentrations and greatly facilitate toxicological studies of the NNK and NNAL. GRAPHICAL ABSTRACT: